Implementasi Teknologi Cloud Storage (Studi Kasus Kantor Kepala Desa Sidoharjo) - Ma'arif, Sandhityas Saiful, Ir. Bana Handaga, M.T., Ph.D (2017)
In this modern era, one of the most common problem is the loss of critical data due to faulty hardware, virus infected file so that the file can not be opened and this problem occurs in the office of the village head Sidoharjo, many employees who complained about the limited storage space and worried files that are susceptible to the virus. Therefore, it is necessary cloud computing services as a storage medium that can back up all data is secured critical and can be uploaded and downloaded from anywhere. OwnCloud has features that can meet the needs of the service in the office of the head of the village, these features include: upluad file, download a file, create a document online, adding more space, file sharing, document edit. Specifications VPS to make the cloud include: intel xeon processor, 2 GB Ram, Hard Drive 20 GB and 1000 GB bandwidth. Testing is done by five users of the village head office employees to access Sidoharjo ownCloud server simultaneously, from these tests can be seen in the server's ability to deliver services to all users who access simultaneously. The result can be seen with an average speed of 150 Kbps for upload accessed via smartphones and to download 320 kbps accessible via pc get 152 kbps for downloading and 400 kbps for upload. The server can provide services to each user in a different time for each user.user.